Synthesis and preliminary anticancer activity of new 1,4-dihydro-3-(3-hydroxy-2-naphthyl)-4-substituted-5H-1,2,4-triazoline-5-thiones - (:unkn) unknown (My University, 2002)
1,4-Dihydro-3-(3-hydroxy-2-naphthyl)-4-substituted-5H-L2,4-triazolinc-5-thiones were synthesized. The structures of original eight compounds were confirmed by elemental analysis, 1H NMR and mass spectral methods. One of the compounds (3a) was tested in vitro for its anticancer activity against 52 human tumor cell lines.
Keywords: Humans; Antineoplastic Agents; Triazoles; Tumor Cells, Cultured; Dose-Response Relationship, Drug; Molecular Structure; Cell Division; Thiones; Magnetic Resonance Spectroscopy; Drug Screening Assays, Antitumor